2016
DOI: 10.1002/stco.201600004
|View full text |Cite
|
Sign up to set email alerts
|

Verification of flexural buckling according to Eurocode 3 part 1‐1 using bow imperfections

Abstract: The resistance of compression members may be calculated by the design buckling resistance based on the reduction factor χ, which depends on the slenderness, or by the cross‐section resistance based on internal forces according to a second‐order analysis taking into account equivalent initial bow imperfections as well. The second way is especially advantageous in the case of axial forces and bending. Values for equivalent initial bow imperfections are given in codes such as Eurocode 3 [5] or DIN 18800 [4]. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 4 publications
0
43
0
7
Order By: Relevance
“…3 shows that values η ul > 1.0 represent results on the unsafe side. c) In [6] it already is proposed and in [5] it is confirmed that for axial compression and flexural buckling about axis y-y, a linear plastic interaction should be used. Axial compression and flexural buckling about axis y-y a) Based on the interaction formula according to EN 1993-1-1, sec.…”
Section: Test Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…3 shows that values η ul > 1.0 represent results on the unsafe side. c) In [6] it already is proposed and in [5] it is confirmed that for axial compression and flexural buckling about axis y-y, a linear plastic interaction should be used. Axial compression and flexural buckling about axis y-y a) Based on the interaction formula according to EN 1993-1-1, sec.…”
Section: Test Resultsmentioning
confidence: 90%
“…6.9.2.1 or the interaction formula according to the proposal by Kindmann/Stroetmann [6], some results around 1.05 occur if only the test series i), ii) or iii) are taken into account: for series i), max η = 1.032; for series ii), max η = 1.050; and for series iii), max η = 1.044. linear plastic N test ultimate load according to the tests mentioned before Eq.…”
Section: Test Resultsmentioning
confidence: 99%
See 3 more Smart Citations